PTH-209 Patient experiences of parenteral nutrition in an acute teaching hospital. (22nd June 2015) - Wyer, NJ; Carpenter, C
Abstract : Introduction: There is a lack of research investigating the experience of patients with intestinal failure (IF) who require parenteral nutrition (PN) in acute care. The NCEPOD national audit (Stewart et al. 2010) demonstrated high levels of complications in patients receiving PN. Furthermore, gastrointestinal symptoms caused by IF require complex regimens of medication and the modification or restriction of fluid and diet. It is recommended that all acute hospitals should have a nutrition team (NICE 2006), however nutrition teams need to better understand how to best support patients receiving PN in hospital. The aim of this study was to explore the patient experiences of receiving PN in the acute healthcare setting. Method: Descriptive phenomenology was the chosen methodology. Purposive sampling was used to recruit ten participants who had received PN for >7 days in an acute teaching hospital. In-depth interviews were conducted, which were audio-recorded. The interviews were transcribed verbatim and qualitatively analysed, guided by Colaizzi's (1978) approach. Results: PN was universally considered positive by patients. It was 'life saving' and they felt it unlikely that they would have survived the hospital admission without it. Three core themes and seven subthemes were identified: Conclusion: Patients who require PN wish to be heard and be involved in decisions about their nutritional care; however healthcare professionals in acute care frequently fail to operate in a patient centred manner. This is particularly evident when several clinical teams are involved and when enteral nutrition is being introduced. When conflicting nutritional advice is given to patients it affects their trust and confidence in the clinical teams. The patient experience whilst on PN could be improved by nutrition teams having greater autonomy regarding the provision of nutritional advice and by providing more support to patients on dealing with the altered relationship with eating. Disclosure of interest: None Declared. References: Colaizzi, P. (1978) Psychological Research as a Phenomenologist Views it. In Existential Phenomenological Alternatives for Psychology . Ed. by Valle, R. and King, M. New York, NY: Oxford University Press, 48–71 NICE (2006) Nutrition Support in Adults: Oral Nutrition Support, Enteral Tube Feeding and Parenteral Nutrition : NICE Stewart JAD, Mason DG, Smith N, Protopapa K, Mason M. A Mixed Bag . An Enquiry into the Care of Hospital Patients Receiving Parenteral Nutrition: NCEPOD, 2010